Pengaruh Ukuran Perusahaan, Political Cost Dan Kinerja Lingkungan Terhadap Environmental Disclosure Dalam Laporan Tahunan - Ulan Noviani, Ni Kadek Dwi Nana; Alit Suardana, Ketut (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
Environmental Disclosure is disclosure made by public companies related to their obligations to the environment and society. This study aims to determine the factors that influence Environmental Disclosure, namely the size of the company, political cots, and environmental performance. The study was conducted at companies listed on the Stock Exchange for the period 2014-2017 which are incorporated in the food and beverage sub-sector. The number of samples taken were 56 companies, with probability sampling methods. Data collection is done through analysis of company financial statements, which are analyzed by multiple linear regression. Based on the results of the analysis it was found that the size of the company partially had a positive effect on Environmental Disclosure. Political Cost has a positive effect on Environmental Disclosure. Environmental performance has a positive effect on Environmental Disclosure. Keywords : Enviromental disclosure, Size, Political Cost, Performance.